INTELLECTUALIZATION OF OPEN EDUCATION SERVICES - Nina V. Komleva; Olga A. Khlopkova (Открытое образование (Москва), 2016)
The article presents the approach of leveling of the main drawbacks of online learning systems associated with diffi culties of objective monitoring of students’ knowledge. This method is based on the integration of the module that combines neural networks and genetic algorithms in the education system architecture with a goal of better examining of incomplete and inaccurate data. There are described the results of this method, which rises e-learning services to a new level of automation, agility and dynamism.